1976
DOI: 10.1007/bf00585891
|View full text |Cite
|
Sign up to set email alerts
|

Single nephron glomerular filtration rate ratios of superficial, intercortical and juxtamedullary nephrons in rats during development

Abstract: In 20, 40 and 60-day-old rats the filtration rate was studied using Baines modification of Hanssen's Na4Fe (14CN)6 method enabeling the determination of single nephron glomerular filtration rate (SNGFR) ratio between superficial (S), intercortical (I) and juxtamedullary (J) nephrons. The proximal tubule lengths were determined as well. A close correlation was obtained between age and S/I, I/J and S/J of proximal tubule lengths and between age and I/J, S/J 14C-activities of ferro-cyanide. Presented findings con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…1) (291; 336). The localization and structural heterogeneity of superficial and juxtamedullary nephrons have been extensively investigated since the 1960s (68; 68; 84; 115; 182; 221; 248; 249; 335; 350; 411; 431; 439). Studies using light and high resolution electron microscopes have demonstrated that nephrons in rodents and humans differ not only in their glomerular localization, but also in their structural characteristics.…”
Section: Classification Of Nephronsmentioning
confidence: 99%
“…1) (291; 336). The localization and structural heterogeneity of superficial and juxtamedullary nephrons have been extensively investigated since the 1960s (68; 68; 84; 115; 182; 221; 248; 249; 335; 350; 411; 431; 439). Studies using light and high resolution electron microscopes have demonstrated that nephrons in rodents and humans differ not only in their glomerular localization, but also in their structural characteristics.…”
Section: Classification Of Nephronsmentioning
confidence: 99%
“…32 Only at that age is the development of the kidney function accomplished by achievement of the adult pattern of distribution of the single-nephron glomerular filtration (SNGFR) . 33 Therefore, SNGFR distribution was estimated in developing Brattleboro rats. Baines 34 modification of Hansen's [14C]ferrocyanide single-injection method was used and the ratios of superficial to juxtamedullary (S/ J) and intercortical to juxtamedullary (I/ J ) nephrons were determined.…”
mentioning
confidence: 99%